Past lives, present miracles - Linn, Denise (Hay House, 2008)
A guide to discovering your past lives without ever doing a regression; removing limitations regarding your relationships, abundance, and health that came from your past lives; uncovering the symptoms of past-life traumas and clearing them; understanding the roles that loved ones played in your previous incarnations; finding your personal guides, spirit guardians, and angels and receiving their help ... and much, much more.